Quality improvements in decreasing medication administration errors made by nursing staff in an academic medical center hospital: a trend analysis during the journey to Joint Commission International accreditation and in the post-accreditation era - Wang HF; Jin JF; Feng XQ; Huang X; Zhu LL; Zhao XY; Zhou Q (Dove Medical Press, 2015)
Hua-fen Wang,1 Jing-fen Jin,1 Xiu-qin Feng,1 Xin Huang,1 Ling-ling Zhu,2 Xiao-ying Zhao,3 Quan Zhou4 1Division of Nursing, 2Geriatric VIP Ward, Division of Nursing, 3Office of Quality Administration, 4Department of Pharmacy, the Second Affiliated Hospital of Zhejiang University, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People’s Republic of China Background: Medication errors may occur during prescribing, transcribing, prescription auditing, preparing, dispensing, administration, and monitoring. Medication administration errors (MAEs) are those that actually reach patients and remain a threat to patient safety. The Joint Commission International (JCI) advocates medication error prevention, but experience in reducing MAEs during the period of before and after JCI accreditation has not been reported. Methods: An intervention study, aimed at reducing MAEs in hospitalized patients, was performed in the Second Affiliated Hospital of Zhejiang University, Hangzhou, People’s Republic of China, during the journey to JCI accreditation and in the post-JCI accreditation era (first half-year of 2011 to first half-year of 2014). Comprehensive interventions included organizational, information technology, educational, and process optimization-based measures. Data mining was performed on MAEs derived from a compulsory electronic reporting system. Results: The number of MAEs continuously decreased from 143 (first half-year of 2012) to 64 (first half-year of 2014), with a decrease in occurrence rate by 60.9% (0.338% versus 0.132%, P<0.05). The number of MAEs related to high-alert medications decreased from 32 (the second half-year of 2011) to 16 (the first half-year of 2014), with a decrease in occurrence rate by 57.9% (0.0787% versus 0.0331%, P<0.05). Omission was the top type of MAE during the first half-year of 2011 to the first half-year of 2014, with a decrease by 50% (40 cases versus 20 cases). Intravenous administration error was the top type of error regarding administration route, but it continuously decreased from 64 (first half-year of 2012) to 27 (first half-year of 2014). More experienced registered nurses made fewer medication errors. The number of MAEs in surgical wards was twice that in medicinal wards. Compared with non-intensive care units, the intensive care units exhibited higher occurrence rates of MAEs (1.81% versus 0.24%, P<0.001). Conclusion: A 3-and-a-half-year intervention program on MAEs was confirmed to be effective. MAEs made by nursing staff can be reduced, but cannot be eliminated. The depth, breadth, and efficiency of multidiscipline collaboration among physicians, pharmacists, nurses, information engineers, and hospital administrators are pivotal to safety in medication administration. JCI accreditation may help health systems enhance the awareness and ability to prevent MAEs and achieve successful quality improvements. Keywords: medication administration, medication errors, nurse, quality improvements